1978
DOI: 10.1111/j.2042-7158.1978.tb13259.x
|View full text |Cite
|
Sign up to set email alerts
|

Corticosterone concentrations in mice during ethanol drinking and withdrawal

Abstract: Consumption of an ethanol-containing diet by mice resulted in a significant increase in circulating concentrations of corticosterone which was maintained for 8 days. There were no changes in the concentrations of plasma corticosterone binding globulin. Ethanol withdrawal symptoms followed theremoval of ethanol from the diet and circulating corticosterone concentrations were further increased. There was no correlation between blood ethanol and glucocorticoid concentrations during the chronic ethanol treatment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
54
0
1

Year Published

1987
1987
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(58 citation statements)
references
References 13 publications
3
54
0
1
Order By: Relevance
“…In fact, when we initially reported that N/OFQ increases circulating ACTH and CORT concentrations in unstressed and mildly stressed rats (Devine et al, 2001), we reconciled our hormonal findings with the published behavioral data (Jenck et al, 1997;Griebel et al, 1999) on the basis that a variety of drugs that are anxiolytic can also increase circulating CORT concentrations in unstressed or mildly stressed rats (Ellis, 1966;Kakihana et al, 1968;Marc and Morselli, 1969;Tabakoff et al, 1978;Rivier et al, 1984;Matheson et al, 1988Matheson et al, , 1997ade Boer et al, 1991). However, the current findings indicate that the behavioral and hormonal effects of N/OFQ resemble the effects of drugs like FG 7142 File, 1985, 1986), yohimbine (Smythe et al, 1983;Suemaru et al, 1989), amphetamine (Knych and Eisenberg, 1979;, and caffeine (Spindel et al, 1983;Fall of which are anxiogenic in neophobic tests of anxiety, and all of which elevate circulating ACTH and/or CORT concentrations after acute administration.…”
Section: Anxiogenic Action Of N/ofqmentioning
confidence: 76%
“…In fact, when we initially reported that N/OFQ increases circulating ACTH and CORT concentrations in unstressed and mildly stressed rats (Devine et al, 2001), we reconciled our hormonal findings with the published behavioral data (Jenck et al, 1997;Griebel et al, 1999) on the basis that a variety of drugs that are anxiolytic can also increase circulating CORT concentrations in unstressed or mildly stressed rats (Ellis, 1966;Kakihana et al, 1968;Marc and Morselli, 1969;Tabakoff et al, 1978;Rivier et al, 1984;Matheson et al, 1988Matheson et al, , 1997ade Boer et al, 1991). However, the current findings indicate that the behavioral and hormonal effects of N/OFQ resemble the effects of drugs like FG 7142 File, 1985, 1986), yohimbine (Smythe et al, 1983;Suemaru et al, 1989), amphetamine (Knych and Eisenberg, 1979;, and caffeine (Spindel et al, 1983;Fall of which are anxiogenic in neophobic tests of anxiety, and all of which elevate circulating ACTH and/or CORT concentrations after acute administration.…”
Section: Anxiogenic Action Of N/ofqmentioning
confidence: 76%
“…The hyperactive HPA axis has also been shown during ethanol withdrawal after long-term exposure in animals and humans (Tabakoff et al, 1978;Wand, 1993). Furthermore, it has been shown that adrenalectomy prevents the development of ethanol preference in rats (Fahlke and Eriksson, 2000).…”
mentioning
confidence: 99%
“…Adrenocorticotropin was measured in 100 l of plasma by using an adrenocorticotropin enzyme-linked immunosorbent assay kit (ALPCO Diagnostics, Windham, NH). Blood ethanol levels were determined (in 20-l samples from the same mice used for the endocrine assays) by head-space gas chromatography, using a Varian, Inc. (Palo Alto, CA) 3800 gas chromatograph as described previously (Tabakoff et al, 1978).…”
Section: Methodsmentioning
confidence: 99%
“…A well established, but sometimes overlooked, fact about the physiologic actions of ethanol is that even modest doses of ethanol in humans or other animals can increase circulating levels of adrenocorticotropin and cortisol or corticosterone (Tabakoff et al, 1978;Rivier et al, 1984;Thiagarajan et al, 1988;Ogilvie et al, 1997).…”
mentioning
confidence: 99%